Effect Of Soil Waterlogging Stress On The Physiological Performance Of Seeds And On The Productivity Of Rye Plants - Marques Gehling, Vânia; Pedó, Tiago; Garbin Martinazzo, Emanuela; Zanatta Aumonde, Tiago; Amaral Villela, Francisco (Agrociencia Uruguay, 2015)
The objectives of this study were to evaluate the effect of waterlogging on seed physiological performance and plant productivity in rye. Our study consisted of three treatments: 1) no waterlogging, 2) a single waterlogging period, and 3) double waterlogging period. Plant productivity was evaluated from the number of spikes per plant, the number of seeds per plant, the number of seeds per spike, and seed yield. Seeds were exposed to a germination test and seed physiological quality was evaluated from the seed germination rate, initial germination rate, germination speed index, electric conductivity, shoot length, primary root length, shoot dry matter and primary root dry matter, and weight per 1000 seeds. The seeds derived from plants not exposed to waterlogging showed a higher germination rate in a shorter period of time and higher germination speed index than those derived from plants that were exposed to waterlogging; however, the weight per 1000 seeds was lower and seedlings had longer shoots and primary roots. The plants that were not exposed to waterlogging had a higher number of spikes per plant, higher number of seeds per plant, higher number of seeds per spike, and better seed yield per plant. Therefore, it was concluded that waterlogging has a negative effect on seed physiological performance in rye and that plant productivity is reduced under long-term waterlogging.